Improving pear (Pyrus spp.) harvest maturity assessment: Integration of color composite indicators and sophisticated multivariate analysis techniques - Zeinab Shafaei-Cherush; Kazem Arzani; Nima Ahmadi; Ali Mokhtassi-Bidgoli; Mahdi Ayyari; Hamid Abdollahi (Journal of Agriculture and Food Research)
Predicting the appropriate maturity index for pear fruit at the time of harvest is crucial for preventing post-harvest losses and preserving fruit quality. This study aims to elucidate the relationships among peel color (p-color), nutraceutical parameters, and dry matter content as harvest indices to establish an effective pear fruit maturity index for harvest. We measured the fruit physicochemical changes, color, and texture during different harvest stages of two commercial pear cultivars: 'Shahmiveh’ (Pyrus communis L.) and 'KS6’ (Pyrus serotina Rehd). The variables under study were categorized into four main blocks: fruit harvest, p-color, nutraceutical, and dry matter. We utilized Multivariate Multiple Factor Analysis (MFA) and Partial Least Square Path Modeling (PLS-PM) to explore and quantify the relationships between the harvest index and the other blocks of variables. The analysis revealed that the harvest index was positively correlated with p-color and nutraceuticals but negatively with dry matter content. Specifically, the fruit maturation process of the ‘KS6’ Asian pear cultivar was more closely associated with dry matter content and then color, whereas for the 'Shahmiveh’ European pear, p-color and nutraceutical parameters showed a stronger correlation with the harvest index. Due to the complexity and multi-dimensionality of harvest maturity, composite indicators provide a more accurate description and assessment. Following this, the PLS-PM and MFA methods are useful for investigating this complicated issue, offering significant insights into determining the optimal harvest index by leveraging composite indicators and variables.